ELECTRONIC BANKING (E-BANKING) AND PERFORMANCE OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - Agustin, Hamdi; Rusby, Zulkifli; Siregar, Amiruddin; Hamdi, Lathifa Miftahul Jannati; Hamdi, Luthfia Ahluljannati (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
One of the cashless transactions implemented by Islamic Commercial Banks in Indonesia is internet banking or Electronic Banking (e-banking). The purpose This study to examine the impact of the implementation of electronic banking (e-banking) on the financial performance of Islamic Commercial Banks in Indonesia. The population of this study consists of all Islamic Commercial Banks in Indonesia from 2013 to 2023. According to the Islamic Banking Statistical Data from the Financial Services Authority (Otoritas Jasa Keuangan) in 2013, there were 11 Islamic commercial banks in Indonesia. Due to mergers of several Islamic banks, this study obtained data from 6 Islamic commercial banks as samples. The research findings indicate that the implementation of Electronic Banking (EB) has a negative effect on Return on Assets (ROA). This result is suspected to be caused by the costs associated with electronic banking services, such as infrastructure, maintenance, and human resources, which require higher expenses compared to the revenue generated from internet banking services. Moreover, the increasing frequency of updates to electronic banking services could potentially lower the bank's profitability (ROA) due to the significant costs associated with updating devices, which in turn reduces income. Overall, the costs incurred by Islamic banks to provide internet banking services involve various large cost components, ranging from system development and maintenance to transaction costs, security, and Sharia compliance. The variables of SIZE, DEPOSIT, NPF, and OEOI have an impact on the performance of Islamic Commercial Banks in Indonesia.